2017
DOI: 10.1590/1414-431x20176372
|View full text |Cite
|
Sign up to set email alerts
|

Is endobronchial ultrasound-guided transbronchial needle aspiration with a stylet necessary for lymph node screening in lung cancer patients?

Abstract: During endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), a needle is commonly used with a stylet, although recently the stylet has been omitted. This prospective study aimed to compare the quality of specimens obtained by EBUS-TBNA performed with and without a stylet. Between November 2013 and November 2014, 131 patients with lung cancer underwent EBUS-TBNA, with a total of 148 mediastinal or hilar lymph nodes sampled both with and without an inner-stylet, yielding 296 cytological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The second prospective study compared a group with 2 samples collected with a stylet followed by 2 samples collected without a stylet with a group using the alternate order of collection for the 4 samples. 177 This study indicated no significant sample adequacy differences when stylet was and was not used. However, although the study compared background blood and clot between the collection methods, the study did not compare amount of benign bronchial cells.…”
Section: Additional Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The second prospective study compared a group with 2 samples collected with a stylet followed by 2 samples collected without a stylet with a group using the alternate order of collection for the 4 samples. 177 This study indicated no significant sample adequacy differences when stylet was and was not used. However, although the study compared background blood and clot between the collection methods, the study did not compare amount of benign bronchial cells.…”
Section: Additional Discussionmentioning
confidence: 69%
“…Two studies that evaluated the use of a stylet compared with no stylet were identified by the literature search. 176,177 In the first prospective randomized single-blind controlled clinical trial, the authors studied 194 lymph node biopsies in 120 patients. 176 Each lymph node was sampled with and without a stylet by alternating the 2 methods and randomizing the order.…”
Section: Additional Discussionmentioning
confidence: 99%
“…Fine needle aspiration (FNA) is a simple, minimally invasive, and highly accurate method widely used in the diagnosis of many organ diseases, including thyroid (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). A stylet can theoretically prevent the lumen of the needle from being blocked by other non-lesion components, including blood, before puncturing into the target lesion, thus allowing fuller aspiration of the target tissue into the needle once the stylet is removed.…”
Section: Introductionmentioning
confidence: 99%
“…Although this assumption of a preference for the use of a stylet seems logical, this assumption has not been demonstrated on an empirical basis. Several studies in other areas of FNA, such as gastrointestinal endoscopy and respiratory endoscopy FNA have shown that the stylet does not improve specimen quality and diagnostic efficiency (3)(4)(5)(6)(7)(8). Besides, some studies have shown that stylet may be associated with an inferior specimen quality (9).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the quality of the aspirate and diagnostic performance of EBUS-TBNA have been found to be similar with or without the use of an internal stylet. [5152]…”
Section: Introductionmentioning
confidence: 99%